2017
DOI: 10.1111/evj.12663
|View full text |Cite
|
Sign up to set email alerts
|

Lamellar events related to insulin‐like growth factor‐1 receptor signalling in two models relevant to endocrinopathic laminitis

Abstract: These results support further investigation of mTORC1/RPS6 signalling as a potential therapeutic target(s) in EMSAL. The Summary is available in Chinese - see Supporting Information.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
58
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(58 citation statements)
references
References 51 publications
0
58
0
Order By: Relevance
“…54 Although the lamellar epithelial cells obviously do not progress past EMT into neoplastic cells, similar epithelial gp130-related signaling driven by IL-6 may lead to the lamellar epithelial cell stretching and separation from the lamellar dermis, the two central histologic findings documented to occur with lamellar failure in both sepsis-related and endocrinopathic laminitis. 31 Importantly, not only has gp130 been reported to work through the same signaling (ie, mTORC1/RPS6) as we have recently reported to occur in the lamellae in the EHC model of endocrinopathic laminitis, 55,56 but we have also recently discovered the same increases in phosphorylated/activated proteins downstream of mTORC1 (eg, p70S6K, RPS6) in the lamellae of ambient/untreated limbs in horses administered OF in the current study (Belknap laboratory, unpublished data) as we reported in the EHC study. 56 Due to the possibility that IL-6-related signaling leads to lamellar failure due to signaling mechanisms downstream of the gp130 receptor, investigation of these downstream signaling mechanisms might lead to the discovery of a novel therapeutic target and an effective pharmaceutical agent for the treatment of not only sepsis-related laminitis.…”
Section: Discussionmentioning
confidence: 85%
“…54 Although the lamellar epithelial cells obviously do not progress past EMT into neoplastic cells, similar epithelial gp130-related signaling driven by IL-6 may lead to the lamellar epithelial cell stretching and separation from the lamellar dermis, the two central histologic findings documented to occur with lamellar failure in both sepsis-related and endocrinopathic laminitis. 31 Importantly, not only has gp130 been reported to work through the same signaling (ie, mTORC1/RPS6) as we have recently reported to occur in the lamellae in the EHC model of endocrinopathic laminitis, 55,56 but we have also recently discovered the same increases in phosphorylated/activated proteins downstream of mTORC1 (eg, p70S6K, RPS6) in the lamellae of ambient/untreated limbs in horses administered OF in the current study (Belknap laboratory, unpublished data) as we reported in the EHC study. 56 Due to the possibility that IL-6-related signaling leads to lamellar failure due to signaling mechanisms downstream of the gp130 receptor, investigation of these downstream signaling mechanisms might lead to the discovery of a novel therapeutic target and an effective pharmaceutical agent for the treatment of not only sepsis-related laminitis.…”
Section: Discussionmentioning
confidence: 85%
“…Details regarding the animal‐level outcomes of this experimental EHC model, including concentrations of serum insulin and plasma glucose measured during the protocol, have been published …”
Section: Resultsmentioning
confidence: 88%
“…Both mTORC1 and AMPK signaling intersect at various nodes with inflammatory pathways, integrating metabolic signals with those governing inflammatory responses . Interestingly, although evidence of activation of mTORC1 signaling in the digital lamellae has been documented in this model, we found no evidence of altered AMPK activation in the same tissue. This could be explained based on the competing influences on AMPK activation that may be present at the cellular level under these experimental conditions; increased glucose availability is well known to decrease AMPK activation, but leptin has been reported to increase AMPK activity through JAK2 signaling .…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Further, the paper in this online collection by Lane et al . has demonstrated that signalling proteins downstream of the IGF‐1R are activated in the lamellae during hyperinsulinaemia . If this pathway can be proven as the disease mechanism, then development of novel treatments for laminitis that aim to block signalling through growth factor pathways should rapidly become feasible and a new surge in research in this rapidly moving field will ensue.…”
mentioning
confidence: 99%